2013
DOI: 10.1096/fj.13-241687
|View full text |Cite
|
Sign up to set email alerts
|

NIH research funding and early career physician scientists: continuing challenges in the 21st century

Abstract: Physician scientists (researchers with either M.D. or M.D.-Ph.D. degrees) have the unique potential to combine clinical perspectives with scientific insight, and their participation in biomedical research has long been an important topic for policymakers and educators. Given the recent changes in the research environment, an update and extension of earlier studies of this population was needed. Our findings show that physician scientists are less likely to take a major role in biomedical research than they wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
124
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(129 citation statements)
references
References 11 publications
2
124
0
3
Order By: Relevance
“…Many studies have unequivocally shown that the numbers of physician-scientists have been in decline for many years [2,46,1012]. In 2003, the number of physicians involved primarily in research was 1.8% compared to 4.6% in 1985 [6].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have unequivocally shown that the numbers of physician-scientists have been in decline for many years [2,46,1012]. In 2003, the number of physicians involved primarily in research was 1.8% compared to 4.6% in 1985 [6].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, fewer physicians are applying for post-doctoral fellowships and early-career mentored-K awards. 13 With this metric of success, a key consideration is to help junior faculty obtain the required research skills and publications to be favorably reviewed. We found that award receipt was nearly equally split between R series and K series grants.…”
Section: Discussionmentioning
confidence: 99%
“…Data from the USA indicated that there has been a decline in the number of clinician-scientists who hold primary appointments in a basic science department [12]. This decline in popularity, combined with the rising average age at which new clinician-scientists obtain their first major research grant (37.0 Yin et al Clinician-Scientist training in Canada years of age in 1985 versus 44.3 years in 2011) [13], present a serious threat to the clinician-scientist career pathway. A study from the University of British Columbia indicated that securing salaries and funding for research were two of the key barriers for newly trained clinician-scientists [14].…”
Section: Current State Of Md-phd Programsmentioning
confidence: 99%